2016
DOI: 10.1074/jbc.m116.746594
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 2 Modulates Susceptibility to Experimental Cerebral Malaria through a CCL17-dependent Mechanism

Abstract: Cerebral malaria is a severe and often fatal complication of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…In vitro, microglial expression of CB 2 receptors is the subject of pathogen-or cytokine-specific regulation [87][88][89]. In a mouse model of cerebral malaria, the CB 2 knockout was also associated with a reduced inflammatory status, highlighting the model-dependent role of CB 2 function [90]. A possible explanation for the discrepancies might be compensatory amplified signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, microglial expression of CB 2 receptors is the subject of pathogen-or cytokine-specific regulation [87][88][89]. In a mouse model of cerebral malaria, the CB 2 knockout was also associated with a reduced inflammatory status, highlighting the model-dependent role of CB 2 function [90]. A possible explanation for the discrepancies might be compensatory amplified signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CBD, along with the antimalarial drug artesunate, is able to increase the survival rate of mice infected with Plasmodium berghei ANKA, and can prevent cognitive deficiency associated with the infection [100]. Interestingly, another study demonstrated that CB2 activation had no beneficial effect in an experimental murine model for cerebral malaria, as CB2 knockout mice presented with a higher survival rate due to a lower parasite load in the brain and lower expression of proinflammatory cytokines such as TNF-α and IFN-γ, in addition to lower hematoencephalic barrier disruption [101]. The mononuclear cell infiltrate was also lower, with fewer CD8+ lymphocytes, in contrast with CD11b+ cells which were found in a higher proportion.…”
Section: Plasmodium Bergheimentioning
confidence: 99%
“…CB2, which is derived from hematopoietic origin cells, mediates cannabinoid‐induced immune modulation . In addition, peripheral anti‐inflammatory effects of the endocannabinoid system are associated with signaling via CB2 . However, these two types of receptors are also important regulators for bone remodeling because they affect the proliferation, differentiation, and maturation of bone cells, such as osteoclasts, osteoblasts, and osteocytes .…”
Section: Introductionmentioning
confidence: 99%
“…(14) In addition, peripheral anti-inflammatory effects of the endocannabinoid system are associated with signaling via CB2. (15,16) However, these two types of receptors are also important regulators for bone remodeling because they affect the proliferation, differentiation, and maturation of bone cells, such as osteoclasts, osteoblasts, and osteocytes. (17)(18)(19)(20) Due to their unique combination of properties, cannabinoid receptors, especially CB2, have been widely studied for the treatment of inflammatory disorders and osteolytic bone damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation